2016
DOI: 10.21273/horttech.26.4.484
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting U.S. Consumer Expenditures of Fresh Flowers and Potted Plants

Abstract: The floral industry has experienced declining sales in the past few decades, causing many to speculate as to the underlying causes. To identify consumers’ spending patterns for fresh flowers and potted plants, we extracted and analyzed quarterly expenditure interview data from the Consumer Expenditure Survey, 1996 to 2013. Our analysis revealed consumption trends over time by age group, and compared the differences in expenditure patterns across states. Additionally, we employed the Heckman two-step mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…The South-North America channel operates via production in South America and import to North America. Although the USA is the third production country in the world, in the past 20 years, cut flower production declined and imports increased [5]. For example, the number of year-round cut flower producers was reduced by 21% from 2013 to 2014 [5].…”
Section: Global Cut Flower and Pot-plant Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…The South-North America channel operates via production in South America and import to North America. Although the USA is the third production country in the world, in the past 20 years, cut flower production declined and imports increased [5]. For example, the number of year-round cut flower producers was reduced by 21% from 2013 to 2014 [5].…”
Section: Global Cut Flower and Pot-plant Productionmentioning
confidence: 99%
“…Although the USA is the third production country in the world, in the past 20 years, cut flower production declined and imports increased [5]. For example, the number of year-round cut flower producers was reduced by 21% from 2013 to 2014 [5]. However, specialty cut flower production in the USA and Canada increased due to a significant increase in consumer demand [6].…”
Section: Global Cut Flower and Pot-plant Productionmentioning
confidence: 99%
“…Millennials, those born between the 1981 and 1991 and reaching young adulthood at the beginning of the 21st century (Merriam-Webster Inc., 2018), may prefer a different type of plant compared with a more mature gardener. Recent research has shown differences in floral expenditures in consumers younger than 40 years old and a need to determine their needs and effective marketing strategies (Zhao et al, 2016). Past research found differences in consumers of different ages in their garden purchase satisfaction and levels of purchase regret and encouraged differing marketing tactics based on age (Behe and Dennis, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Identical to Byrne et al [27], except the price variable, who examined the expenditure patterns of U.S. households for FAFH from 1982 to 1989. Zhao et al [28] retained the same variables to evaluate the U.S. consumer expenditure patterns for fresh flowers. Recently, Cheng et al [29] included the four types of variables to estimate demand for nuts in the U.S. Dettmann and Dimitri [30] had only focused on the socio-demographic characteristics to examine the expenditure patterns of U.S. consumers of organic vegetables.…”
Section: Data Descriptionmentioning
confidence: 99%